Changes of enzyme activity and gene expression in embryonic zebrafish co-exposed to beta-cypermethrin and thiacloprid. (January 2020) - Wang, Yanhua; Li, Xinfang; Yang, Guiling; Weng, Hongbiao; Wang, Xinquan; Wang, Qiang
Abstract: Pesticides often occur as mixtures of complex compounds in water environments, while most of studies only focus on the toxic effects of individual pesticides with little attention to the joint toxic effects. In the present study, we aimed to the mixture toxicity of beta -cypermethrin (BCY) and thiacloprid (THI) to zebrafish ( Danio rerio ) employing multiple toxicological endpoints. Results displayed that the 96-h LC50 values of BCY to D. rerio at various developmental stages ranged from 2.64 × 10 (1.97 × 10–3.37 × 10) to 6.03 × 10 3 (4.54 × 10 3 –1.05 × 10 4 ) nM, which were lower than those of THI ranging from 2.97 × 10 4 (1.96 × 10 4 –4.25 × 10 4 ) to 2.86 × 10 5 (2.19 × 10 5 –5.87 × 10 5 ) nM. Mixtures of BCY and THI exhibited synergistic response in embryonic zebrafish. Meanwhile, the enzyme activities of antioxidants (CAT and SOD) and detoxification enzyme (CarE), endogenous T-GSH and MDA contents, as well as gene expressions ( tsh, crh, cxcl and bax ) involved in oxidative stress, cellular apoptosis, immune system and endocrine system were obviously changed in the mixture exposure compared with the respective BCY or THI treatment. Consequently, the increased toxicity of pesticide mixture suggested that the toxicological data acquired from individual pesticide tests might underrate the toxicity risk of pesticides that actually arise in the real environment. Taken together, our present study provided evidence that mixture exposure of BCY and THI could induce additional toxic effect compared with their respective individual pesticides on D. rerio, offering valuable insights into the toxic mechanism of pesticide mixture. Graphical abstract: Image 1 Highlights: Beta -cypermethrin exerted greater toxicity than thicloprid to zebrafish. Mixtures of beta -cypermethrin and thicloprid had synergistic effect on zebrafish. Expressions of 4 genes exerted greater changes in pesticide mixtures. Mixture effects should be considered in the ecological risks of pesticide. Abstract : Synergistic effects and underlying mechanism of beta -cypermethrin and thiacloprid on zebrafish.